Evolution of RAS Mutational Status in Liquid Biopsies During First-Line Chemotherapy for Metastatic Colorectal Cancer - Klein-Scory, Susanne; Wahner, Ingo; Maslova, Marina; Al-Sewaidi, Yosef; Pohl, Michael; Mika, Thomas; Ladigan, Swetlana; Schroers, Roland; Baraniskin, Alexander (Frontiers in Oncology, 2020)
Treatment options for patients with metastatic colorectal cancer (mCRC) are limited. This particularly affects the main group: patients with RAS mutations, who should not be considered eligible for therapy with EGFR antibodies. In this liquid biopsy-based study, we performed the first in-depth analysis of the course of mutational status in initially RAS-mutated patients during first-line therapy. RAS mutation status of twelve patients with initially RAS-mutated mCRC was monitored longitudinally in 69 samples and narrow-meshed using liquid biopsy. We focused on patients with stable disease (SD) or partial remission (PR) as response to first-line therapy (11 patients). Detection of fragmented RAS-mutated circulating cell free tumor DNA (ctDNA) in plasma was performed by digital droplet PCR (ddPCR) and BEAMing. Patients’ total tumor masses were determined by measuring the tumor volumes using CT scan data. All patients with PR or SD at first follow-up revealed a consistent decrease of RAS mutation load. The ctDNA-based RAS mutation status of ten patients (91%) 10 patients from 11) even converted to wild type in ddPCR. Remarkably, the conversion was observed already after the first cycle of chemotherapy. In patients with initially RAS-mutated mCRC, RAS mutations rapidly disappeared during first-line therapy in liquid biopsy, independent of type and intensity of chemo- and anti-VEGF therapy. This novel observation raises the important question whether these patients may benefit from treatment with anti-EGFR antibodies analogous to RAS wild type tumors following conversion of initial RAS-mutated status.